Shadow Policy-Making: Legal Analysis of Unwritten Policies in Modern Government - Salintohe, Olivia; Lumeno, Suzanna; Taroreh, Erwin (PT. Anagata Sembagi Education, 2025)
Contemporary governance practices increasingly rely on unwritten policies (shadow policies), such as informal directives, internal memoranda, and bureaucratic practices that function as de facto regulatory norms. Despite their direct impact on citizens’ rights, these unwritten policies lack explicit legal recognition within Indonesia’s administrative law framework. This study aims to analyze the legal status of shadow policies and examine the implications of normative gaps on the principle of legality, good governance principles, and the legal protection of citizens. Employing a normative juridical method with statutory, conceptual, and case approaches, this research finds a regulatory vacuum in Law No. 30 of 2014 on Government Administration and Law No. 12 of 2011 on the Formation of Laws and Regulations. This vacuum blurs the distinction between lawful discretion and informal policies, resulting in legal uncertainty, weakened accountability, and limited judicial oversight. The study concludes that normative reform is essential to regulate shadow policies in a controlled manner in order to strengthen legal certainty, protect citizens’ rights, and uphold the rule of law.